Comparative analysis of three decades' experience in the management of pregnant women with epilepsy: a real-life scenario - Válóczy, Réka; Fekete, István; Horváth, László; Mészáros, Zsófia; Fekete, Klára (Frontiers in Neurology, 2023)
Introduction People with epilepsy have to face many challenges, including regular follow-ups, the need to take antiseizure medications (ASMs), and the fear of seizures. Pregnant women with epilepsy (PWWE) are a special group with even more challenges because they are responsible for the fetus. We aimed to evaluate the change in the frequency of pregnancies over the years and the possible role of newer types of ASMs concerning this change, the shift in medication use over three decades, and their possible impact on the outcome of the observed pregnancies. Methods Data were retrieved from the prospective Epilepsy Database of the Outpatient Clinic at our tertiary center between 1 January 1992 and 31 December 2020. Groups were formed for comparison in time and depending on whether regular care consultation was our task. Statistical analysis was carried out using Microsoft Office Excel 2021. Basic statistics and categorical variables were assessed using Pearson's χ2 test with Yates' correction. Differences were considered significant if the p-value was <0.05. The odds ratio and 95% confidence intervals were calculated wherever needed. Results Altogether, 181 pregnancies were studied, mostly after 2002. The regular follow-up group consisted of 101 patients, with 44.5% presenting in the first trimester. The majority of seizures were either generalized or focal to bilateral tonic-clonic seizure types (85.6%). Pregnancies ended in live births in 91.7%, which gradually improved over time, while spontaneous abortion did not differ significantly in the time interval groups. Mostly, monotherapy was provided. PWWEs had higher chances for seizure freedom in the regular-care group I: OR = 2.9 (2.15–3.65) p < 0.0001. A shift toward newer-type ASMs was found as time passed. Levetiracetam and lamotrigine were more commonly used in the regular care group I than by those patients who were sent to consultation only and not treated at our center [OR = 3.18 (2.49–3.87)] p < 0.0001. Conclusion This is the first study in our region to evaluate experience in the treatment and outcome of PWWE. Having received reliable care and safer ASMs, the number of pregnancies among PWWEs grew. Data suggested that specialized centers' care offered cooperation with obstetricians is important. Moreover, professional care can also enable PWWEs to have uneventful pregnancies.